Toxoplasmose congênita: seguimento do primeiro ano de vida de lactentes provenientes de surto na cidade de Santa Maria – RS em 2018 - Piccini, Júlia Danezi (2021)
Congenital toxoplasmosis is a severe disease, usually asymptomatic at birth, but which can cause ocular damage, such as chorioretinitis and neurological involvement, such as brain calcifications and microcephaly. The outbreak of toxoplasmosis in Santa Maria, RS in 2018 was considered the largest worldwide outbreak of the disease to date, and consequently the one with the most affected infants. Objective: Evaluate infants with congenital toxoplasmosis from an outbreak that occurred in Santa Maria - Brazil, in 2018. Methods: Longitudinal analytical, cohort study, involving infants diagnosed with congenital toxoplasmosis during 2018, in Santa Maria - Brazil, in follow-up at the Pediatric Infectious Disease Clinic of Hospital Universitário de Santa Maria. Performed in two stages: retrospective, with secondary data collected from medical records, and prospective, with ophthalmological and neuropsychomotor development (NPMD) assessment during follow-up consultations at 9 and 12 months of age. Results: Of the total number of infants, 75% had comorbidities in addition to congenital toxoplasmosis, being that one (5%) died at 5 months of age due to congenital toxoplasmosis complications. At 9 months, 33.4% of infants had adequate NPMD, 61.1% were at risk of delay and one (5.5%) had delayed NPMD. At 12 months, 55% had adequate NPMD, 30% risk of delay and 10% delay of NPMD. All infants with adequate NPMD at 9 months had normal cranial CT at birth; 75% of the children at risk of delay in the NPMD at 9 months had abnormal cranial CT at birth, as well as 100% of those classified as delayed (p = 0.058). At 12 months, 28.6% of children with normal NPMD had abnormal cranial CT at birth, as well as 100% of children at risk or in delay (p = 0.051). At the initial assessment, at birth, 65% of newborns did not have ocular changes and 35% already had lesions, with chorioretinitis being the most frequent. During follow-up, there was an increase in the percentage of infants with ocular damage to 70%. The infants who did not tolerate the treatment, have not showed ocular damage during the follow-up (p = 0.11), and only one showed risk / delay in the NPMD at 12 months. Treatment tolerance was observed in 87.5% of children with altered NPMD (p = 0.73). Conclusion: Congenital toxoplasmosis had an important impact, showing ocular and neurological involvement in more than half of the children studied. It was not possible to observe a significant association between low treatment tolerance and a higher rate of ocular alteration and neuropsychomotor development.